2017
DOI: 10.16965/ijpr.2017.179
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Kinesiophobia on Quality of Life in Subjects With Low Back Pain: A Cross-Sectional Study

Abstract: Background: Studies has demonstrated the development of Kinesiophobia in Low Back Pain (LBP) and identified as one of the risk factor for chronicity in LBP. In addition to deconditioning effect, Kinesiophobia also install functional disability and does that affect quality of life? Literatures had exposed the association of Kinesiophobia in chronic and acute low back pain separately but paucity in estimating their quality of life thus this study aims to explore the impact of Kinesiophobia on the quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
0
1
2
Order By: Relevance
“…Previous literatures also found that there is positive correlation between pain and kinesiophobia. [7,9,12,13] In present study, there is no correlation found between pain and physical activity. Previous study by Verbunt et.…”
Section: Discussioncontrasting
confidence: 66%
“…Previous literatures also found that there is positive correlation between pain and kinesiophobia. [7,9,12,13] In present study, there is no correlation found between pain and physical activity. Previous study by Verbunt et.…”
Section: Discussioncontrasting
confidence: 66%
“…Vlaeyen set al (1995) nurodo, kad didesnis nei 37 balų rodiklis rodo didelę judesio baimę. Pasak Pitchai et al (2017), yra tiesioginis ryšys tarp skausmo ir kineziofobijos lygio asmenų, kurie jaučia lėtinį ANDS. Be to, aukštesnis judesio baimės lygis didina funkcinės negalios tikimybę, o tai žymiai pablogina gyvenimo kokybę (Pitchai et al, 2017).…”
Section: Rezultatų Aptarimasunclassified
“…Pasak Pitchai et al (2017), yra tiesioginis ryšys tarp skausmo ir kineziofobijos lygio asmenų, kurie jaučia lėtinį ANDS. Be to, aukštesnis judesio baimės lygis didina funkcinės negalios tikimybę, o tai žymiai pablogina gyvenimo kokybę (Pitchai et al, 2017). Šio tyrimo duomenimis, vidutinis tiriamųjų judesio baimės lygis po 10 kineziterapijos užsiėmimų sumažėjo 5,5 4,7 balo.…”
Section: Rezultatų Aptarimasunclassified